INTERSTELLAR MATTER IN CHONDRITES - Lavrukhina A.K. (My University, 2004)
Small amounts of interstellar grains which survived processes in the protoplanetary nebula were identified in carbonaceous and unequilibrated chondrites. The stellar origin of the diamond, graphite, SiC, and corundum grains is suggested by their extremely anomalous isotopic compositions of a nucleogenic character and peculiar compositions of inert gases. Their investigation provides valuable information on the nuclear and physicochemical processes during the early stages of the genesis of solar system matter. Of special interest is the investigation of individual grains, which provides insight into the particular sources of the nucleosynthesis of pure components and their mixtures represented in the composition of chondrites.